Combined effects of physical activity and sedentary behavior on all-cause mortality in heart failure patients: A cohort study of national health and nutrition examination survey analysis - Zhu, Yunhui; Chen, Zhebin; Chen, Songzan; Fu, Guosheng; Wang, Yao (Frontiers in Cardiovascular Medicine, 2022)
Background Physical activity and sedentary behavior are independently related to the risk of cardiovascular disease. Physical activity is recognized as having a protective effect, while being sedentary seems to be adverse. Nonetheless, the interactions between physical activity and sedentary behavior and the combined effect on the prognosis of heart failure patients remain unclear. Methods and results This cohort study included 886 heart failure patients from the National Health and Nutrition Examination Survey (NHANES) 2007-2018. Physical activity and sedentary behavior were assessed by the NHANES questionnaires. The all-caused deaths of enrolled subjects were identified from National Death Index (NDI) database. During a median follow-up of 51 months, 321 (36.2%) deaths from any causes occurred. Multivariable Cox proportional hazards models were used to estimate the hazard ratios (HRs) and 95% confidence interval (CI) for the all-cause mortality in heart failure patients associated with physical activity and sedentary behavior. Physical activity was independently associated with lower mortality [HR = 0.51, 95% CI (0.38-0.68), p < 0.001] and sedentary behavior was associated with adverse prognosis [HR = 1.79, 95% CI (1.41–2.28), p < 0.001]. Kaplan–Meier survival curve showed that physical activity appeared to attenuate the negative consequences of SB, while sedentary behavior increased the all-cause mortality, particularly those without physical activity. Conclusion Physical activity has a protective effect on HF patients’ prognosis, particularly those with sedentary behavior. Sedentary behavior independently exhibited a negative association in populations without physical activity, while it does not increase mortality in those with moderate physical activity.